Bovine cryptosporidiosis1 - Teixeira, Weslen Fabricio Pires [UNESP]; Prando, Luciana [UNESP]; Oliveira, Bruno César Miranda [UNESP]; De Matos, Lucas Vinicius Shigaki [UNESP]; Pierucci, Julia Cestari [UNESP]; Lopes, Welber Daniel Zanetti; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Cryptosporidiosis is a cosmopolitan protozoonosis infection caused by coccidia of the genus Cryptosporidium. The infection in cattle is caused mainly by the following species of parasite: Cryptosporidium parvum, Cryptosporidium bovis, Cryptosporidium andersoni and Cryptosporidium rynae. Clinical signs in bovine cryptosporidiosis are directly correlated to host's age and immune status as well as parasite species causing the infection. Diarrhea is the most evident clinical sign in cattle infected by the protozoan, being almost always present in the early life of the animal, when its immunity is not completely developed. The occurrence of diarrhea in newborn calves is usually attributed to C. parvum, which, among the species of Cryptosporidium affecting cattle, is the one with greater epidemiological importance for both animal and human cryptosporidiosis. The epidemiology of Cryptosporidiosis is closely connected with the presence of the parasite oocysts in the environment, being the infected cattle able to disseminate, through its feces, large amounts of this parasitic form during infection period. Knowledge regarding transmission, diagnosis and control of bovine and human cryptosporidiosis should be passed on to population as a basic control measure of this disease.
Keywords: Cryptosporidium; Diarrhea; Oocysts